HER2-directed therapy following ctDNA-identified ERBB2 amplification in patients with advanced gastroesophageal cancer: exploration of real-world outcomes - S. Chakrabarti; L. Bucheit; J. Saha; K. Clemens; R. Barnett; N. Zhang; A. Mahipal (ESMO Gastrointestinal Oncology, 2024)
Background: Data on patient outcomes with human epidermal growth factor receptor 2 (HER2)-directed therapy after detection of ERBB2 amplification (ERBB2 amp) by circulating tumor DNA (ctDNA) are lacking in advanced gastroesophageal adenocarcinoma (aGEA). We report real-world outcomes in aGEA patients who received HER2-directed therapy following ctDNA-identified ERBB2 amp. Materials and methods: Real-world evidence was sourced from the GuardantINFORM (Guardant Health) database which includes aggregated health claims and de-identified results from patients undergoing ctDNA testing [Guardant360 (G360)]. Patients with aGEA, ERBB2 amp, and one or more claims for treatment after index G360 were included; those with prior HER2-directed therapy were excluded. Real-world time to treatment discontinuation (rwTTD), real-world time to next treatment (rwTTNT), and real-world overall survival (rwOS) were assessed in months. The Cox regression model adjusted for age, gender, and lines of treatment since diagnosis assessed differences in outcomes. Results: We identified 215 patients with ERBB2 amp, out of which 135 (63%) received HER2-directed therapy following ctDNA-identified ERBB2 amp. rwTTD and rwTTNT were significantly improved in patients receiving HER2-directed therapy compared with those who did not [rwTTD: 5.8 versus 1.9 months, hazard ratio (HR) 0.47, 95% confidence interval (CI) 0.34-0.65, P < 0.01; rwTTNT: 9.4 versus 6.3 months, HR 0.55, 95% CI 0.37-0.81, P < 0.01]. No differences in rwOS were observed (rwOS: not reached versus 22 months, HR 0.67, 95% CI 0.41-1.08, P = 0.10). Conclusions: Detection of ERBB2 amp by ctDNA testing is feasible and may confer improved outcomes in patients receiving HER2-directed therapy, presenting an opportunity to increase HER2-directed therapy utilization in patients with aGEA.